The implementation of multicultural education in Indonesian elementary education system - Bahtiar, Reza Syehma; Wuryandani, Wuri; Sujarwo, Sujarwo; Wibowo, Amiruddin Hadi; Suryarini, Diah Yovita (Edelweiss Applied Science and Technology, 2024)
Known as multi-ethnic country, Indonesia, may face multi-cultural challenge if it is not managed properly. Accordingly, multi-cultural education required in the early stage of education, in elementary school. This paper aims to describe what multicultural education means in the Indonesian elementary education system, and how it is implemented. This study used literature review research design to review various literatures and see the multicultural system within teaching and learning in Indonesia. The data collected from various literatures of previous research on multicultural education and Indonesian elementary education system. Teachers should adjust their teaching to be more equitable and depend less on teacher-centric relations, and provide more room for students to participate in multicultural activities. Additionally, it is seen that multicultural education should not only be limited to a course subject, but embedded in every aspect of elementary education. Insights from this analysis offers an approach to the implementation of multicultural education in Indonesian elementary education system.